Allelic association under map error and recombinational heterogeneity: A tale of two sites - Lonjou, Christine (The National Academy of Sciences, 1998)
Recombination acts on the genetic map, not on the physical map. On the other hand, the physical map is usually more accurate. Choice of the genetic or physical map for positional cloning by allelic association depends on the goodness of fit of data to each map under an established model. Huntington disease illustrates the usual case in which the greater reliability of physical data outweighs recombinational heterogeneity. Hemochromatosis represents an exceptional case in which unrecognized recombinational heterogeneity retarded positional cloning for a decade. The Malecot model performs well for major genes, but no approach assuming either equilibrium or disequilibrium has been validated for oligogenes contributing to common disease. In this case of greatest interest, the power of allelic association relative to linkage is less clear than for major genes.